FTO is Associated with Patient Prognosis and Immune Infiltrates in Gastric Cancer and Regulates TGF-β Expression - Lai, Huan; Hu, Nan; Zhang, Miao; Jiang, Weiwei; Han, Yiqian; Mao, Chenxi; Zhou, Kangjie; Zhang, Jingzhou; Hong, Yidong; Wu, Fenglei (Combinatorial Chemistry & High Throughput Screening, 2025)
ObjectiveThis study aimed to examine the associations of FTO expression with prognosis, tumor microenvironment (TME), immune cell infiltration, immune checkpoint genes, and relevant signaling pathways in GC. Furthermore, the relationship between FTO and TGF-β was studied in GC.MethodsThe mRNA expression and clinical survival data of GC samples were obtained from The Cancer Genome Atlas Stomach Adenocarcinoma (TCGA-STAD). TIMER2, TNM plot, and GEPIA database were used to analyze FTO expression. The associations of FTO with prognosis and clinicopathologic features were assessed using the Kaplan-Meier plotter and UALCAN database, respectively. The R software was employed to analyze its related signaling pathways and the associations with TME, immune cell infiltration, and immune checkpoint genes. GEPIA and ENCORI were used to examine the association of FTO with TGF-β expression. The SRAMP website was utilized to predict m6A modification of TGF-β. IHC, Western blot, and qPCR were used to analyze the expression levels of FTO and TGF-β in clinical gastric cancer tissue samples or gastric cancer cell lines. In addition, a m6A RNA methylation assay kit was used to determine m6A levels in gastric cancer cells.ResultsFTO mRNA and protein levels were significantly elevated in GC compared to normal gastric tissues. Kaplan-Meier survival analysis suggested that upregulated FTO was associated with a worse prognosis in GC. Upregulated FTO was markedly correlated with differentiation degree, lymph node metastasis, and clinical TNM stage. GO and KEGG pathway analyses revealed that FTO-associated molecules were enriched in neuroactive ligand-receptor interaction, calcium signaling, PI3k-Akt signaling, cAMP signaling pathways, and TGF-β signaling pathways, among others. The TME score was remarkably higher in the high-FTO group than in the low-FTO group. Furthermore, FTO expression had positive correlations with different types of immune cells and immune checkpoint genes. Moreover, FTO may regulate TGF-β in an m6A RNA modification manner in GC.ConclusionFTO may become an independent predictive prognostic biomarker correlating with TME, immune cell infiltration, and immune checkpoint genes in gastric cancer and might influence GC progression by regulating TGF-β expression.
Keywords: prognosis